A comprehensive survey of false data injection in smart grid. (5th January 2015) - Guan, Zhitao; Sun, Nan; Xu, Yue; Yang, Tingting
The smart grid has attracted great attention in the recent years. It is poised to transform a centralised, producer–controlled network to a decentralised, consumer–interactive network supported by fine–grained monitoring. However, owing to the interactive nature of the smart grid, it faces the threat of being attacked. False data injection is a rapidly growing problem in smart grids. The multitude and variety of both the attacks and the defence approaches are overwhelming. In this paper, the attacks and countermeasures about false data injection in smart grids are discussed and analysed in detail. The attack classification criteria were selected to highlight commonalities and important features of the power grid. The attacks are classified as attacks based on Direct Current (DC) power model, Alternating Current (AC) power model and control system model; the countermeasures are classified as attack detection methods and new state estimation methods. With a better understanding of the problem and the current solution space, some existing problems and the future work are discussed in detail.